ANTI-VIBRATION OPTIMIZATION DESIGN FOR CLAMP-LIFTING DEVICE ON AIRCRAFT TRACTORS - GAO QingZhen; HUANG An; SHI PeiCheng (Jixie qiangdu)
In order to solve the vibration problem of clamp-lifting device, the joint mechanical analysis and modelings including clamp-lifting device, wheel and landing gear were carried out, and the system vibration differential equations including stiffness and damping characteristics of components were obtained by the frequency response method. The system vibration characteristics under an external displacement disturbance in horizontal and vertical directions were studied by MATLAB simulation.Then the influence of element stiffness and damping characterstics on device vibration was analyzed. The anti-vibration design and effect verification of the clamp-lifting device were carried out through ANSYS calculation and vibration simulation. The results show that the restraint mode and load distribution on wheels are optimized, the device stiffness is improved, the device deformation under load is reduced to 1/3 of the original, and the device vibration amplitude and time are reduced by more than 50% when disturbed. The 1 st～6 th order modal analysis shows that the resonance possibility of lifting plate is low. The research can provide a useful reference for an anti-vibration design in aircraft traction.